Traumatic brain injury and grey matter concentration: a preliminary voxel based morphometry study - Gale, S D; Baxter, L; Roundy, N; Johnson, S C (Journal of neurology, neurosurgery and psychiatry, 2005)
Background: Magnetic resonance imaging (MRI) studies have shown diffuse cerebral atrophy following traumatic brain injury. In the past, quantitative volumetric analysis of these changes was carried out by manually tracing specific regions of interest. In contrast, voxel based morphometry (VBM) is a fully automated technique that allows examination of the whole brain on a voxel by voxel basis. Objective: To use VBM to evaluate changes in grey matter concentration following traumatic brain injury. Methods: Nine patients with a history of traumatic brain injury (ranging from mild to severe) about one year previously were compared with nine age and sex matched healthy volunteers. T1 weighted three dimensional MRI images were acquired and then analysed with statistical parametric mapping software (SPM2). The patients with traumatic brain injury also completed cognitive testing to determine whether regional grey matter concentration correlated with a measure of attention and initial injury severity. Results: Compared with controls, the brain injured patients had decreased grey matter concentration in multiple brain regions including frontal and temporal cortices, cingulate gyrus, subcortical grey matter, and the cerebellum. Decreased grey matter concentration correlated with lower scores on tests of attention and lower Glasgow coma scale scores. Conclusions: Using VBM, regions of decreased grey matter concentration were observed in subjects with traumatic brain injury compared with well matched controls. In the brain injured patients, there was a relation between grey matter concentration and attentional ability.